Aprotic Heterocyclic Anion Triazolide Ionic Liquids – A New Class of Ionic Liquid Anion Accessed by the Huisgen Cycloaddition Reaction - Thompson, Robert L.; Damodaran, Krishnan; Luebke, David; Nulwala, Hunaid (Synlett, 2013)
The triazole core is a highly versatile heterocyclic ring which can be accessed easily with the Cu(I)-catalyzed Huisgen cycloaddition reaction. Herein we present the preparation of ionic liquids that incorporate a 1,2,3-triazolide anion. These ionic liquids were prepared by a facile procedure utilizing a base-labile pivaloylmethyl group at the 1-position, which can act as precursors to 1H-4-substituted 1,2,3-triazole. These triazoles were then subsequently converted into ionic liquids after deprotonation using an appropriate ionic liquid cation hydroxide. The densities and thermal decompositions of these ionic liquids were measured. These novel ionic liquids have potential applications in gas separations and in metal-free catalysis.
Keywords: ionic liquids; triazoles; triazolides; aprotic heterocyclic anions; CO2 capture; click chemistry